LAND USE PLANNING MEASURES TO SOLVE THE PROBLEM OF UNUSED AND UNCLAIMED FARMLAND IN POST-SOVIET RUSSIA - Lipski, Stanislav; Fatkulina, Anna (THE INNOVATION ECONOMY, 2024)
The article reveals the current problems of unused and unclaimed agricultural land in Russia. The importance of land resources in ensuring the country's food security is shown. The current scale of non-use of agricultural land in different regions is analyzed. It is concluded that the continued existence of a significant number of unclaimed shares (and the corresponding areas of farmland) has become a purely Russian phenomenon. It is proposed that, to a greater extent, future work in this area should be based on land management decisions that are closely related to the current situation in land use. Land managers must ensure the implementation of the State Program for bringing unused land into circulation. The importance of “updating” the entire system of domestic land management is shown. Scientific research has been carried out in the field of land management support for the redevelopment of abandoned lands. Legal research on generalization and analysis of the provisions of legislation on the turnover of agricultural land is characterized. To solve these problems, it is also necessary to ensure the management of agricultural land use by highly qualified specialists, as well as to adopt a new version of the Law on Land Management.